REPRESENTASI WANITA DALAM POSTER IKLAN PENGHARUM PAKAIAN “DOWNY”: KAJIAN SEMIOTIKA PEIRCE - Shifa Nur Zakiyah; Dian Indira; Riza Lupi Ardiati; Ypsi Soeria Soemantri (Kajian Linguistik dan Sastra, 2021)
This research is motivated by the researcher's interest in the "Downy" clothing fragrance advertisement poster which has a variety of different themes so that they want to find out more about the meaning of the depiction on the advertisement poster. The purpose of this study is to describe the representation of women on the "Downy" branded clothing fragrance advertisement poster. This study uses a descriptive qualitative method. The data collection method used in this research is the referential method. The technique used to analyze the data is the matching technique with the informal presentation method. The data is taken from the advertisement poster for the clothing fragrance "Downy" with the theme of women with a different appearance taken from the Facebook "Downy Indonesia". The theory used in this study is the semiotic theory of Charles Sander Peirce to examine icons, indexes,  and symbols or commonly known as trichotomy theory. The results of the analysis show that the advertising poster for "Downy" clothing fragrances represents women as innocent, beautiful and feminine. Women also appear elegant, luxurious and confident with expensive fragrances. In addition, a woman when she becomes a mother will protect her family from everything, including everything that will be used by the family. Through the representation of women on each advertising poster, the product has succeeded in introducing and influencing consumers, especially women, to use “Downy” clothing fragrance.Keywords: semiotics, Peirce, Downy advertising, representation, women.